Jamaica Consumer Protection and Financial Literacy - World Bank (Washington, DC, 2015)
This technical note is based on a mission conducted from April 24 to May 9, 2014 to Kingston and other parts of Jamaica. The mission also conducted a short mystery shopping exercise with the assistance of a representative from the national consumer’s league. Valuable comments on the draft note were provided by the Bank of Jamaica and the Financial Services Commission. The technical note consists of findings, issues and recommendations, and four annexes: annex one, existing structure for prudential and consumer protection supervision; annex two, current and revised legislation affecting financial consumer protection; annex three, comparison to world bank good practices on financial consumer protection; and annex four, national program of consumer protection and financial literacy, implementation plan components. The key recommendations present targeted measures that can be immediately implemented and will have a positive (and measurable) impact on public confidence in formal financial institutions. The focus of the technical note is on deposit-taking institutions although some aspects of others parts of the financial sector have been included.